2011
DOI: 10.1093/jopart/mur030
|View full text |Cite
|
Sign up to set email alerts
|

Parsing Public/Private Differences in Work Motivation and Performance: An Experimental Study

Abstract: This article echoes recent calls for public management research to focus on core questions and utilize multiple methods to advance the state of knowledge in the field. In this article, we call for more experimental research on the public/private distinction, which is a core public management research topic. We then conduct a pilot experimental study that provides new insights-and what seem to be major implications-about this important topic. Specifically, we study individuals' vigilance when performing work in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
71
1
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(75 citation statements)
references
References 28 publications
2
71
1
1
Order By: Relevance
“…Traditionally, there has not been much experimental work within mainstream public administration scholarship. Recently, there have been calls for more experimental research designs, and more experimental work is appearing within the literature (e.g., Brewer 2011;James 2011;Moynihan 2006;Kelman 2007). Building on these recent suggestions, the work serves as a stepping-stone in advancing use of mixed-experimental methods in public administration.…”
Section: Methodsmentioning
confidence: 96%
“…Traditionally, there has not been much experimental work within mainstream public administration scholarship. Recently, there have been calls for more experimental research designs, and more experimental work is appearing within the literature (e.g., Brewer 2011;James 2011;Moynihan 2006;Kelman 2007). Building on these recent suggestions, the work serves as a stepping-stone in advancing use of mixed-experimental methods in public administration.…”
Section: Methodsmentioning
confidence: 96%
“…A recent review (Brewer & Brewer, 2011) found only a handful of true experimental studies published in journals that directly assessed the field of public administration between 1997 and 2011 (Knott, Miller, & Verkuilen, 2003;Landsbergen, Coursey, Loveless, & Shangraw Jr, 1997;Nutt, 2006;Scott, 1997;Scott & Pandey, 2000). A recent review (Brewer & Brewer, 2011) found only a handful of true experimental studies published in journals that directly assessed the field of public administration between 1997 and 2011 (Knott, Miller, & Verkuilen, 2003;Landsbergen, Coursey, Loveless, & Shangraw Jr, 1997;Nutt, 2006;Scott, 1997;Scott & Pandey, 2000).…”
Section: Theoretical Contributionsmentioning
confidence: 99%
“…While public management instruction focuses on organizational theory and behavior, which mainly centers on internal mechanisms of the organization, external influences stemming from publicness present additional challenges-and opportunities-to effective management and organizational performance. By harnessing the multiple factors of publicness, practitioners across sectors can help positively steer the direction of organizational behavior (Brewer and Brewer, 2011;Wheeler and Brady, 1998;Wittmer and Coursey, 1996) and performance Johansen and Zhu, 2014;Petrovsky, James & Boyne, 2015;Walker and Bozeman, 2011).…”
Section: Discussionmentioning
confidence: 99%